Call and Consequences : A Womanist Reading of Mark - St. Clair, Raquel Annette (Book collections on Project MUSE., 2008)
"The son of man must suffer," Jesustells his disciples in the Gospel ofMark, and interpreters agree thiswarning is centrally important to theGospel. But why must Jesus suffer, andwhy must his disciples face sufferingif they would follow him? Is this amatter of "divine necessity," or theconsequence of historical opposition toJesus' cause?Raquel St. Clair brings a womanistperspective to these questions, notingthat marginalized persons, particularlywomen of color, have too oftenexperienced the call to discipleshipas a call simply to "suffering, shame,and surrogacy." Her close reading ofthe Gospel of Mark highlights theimportance of freely accepting theconsequences of answering Jesus' call.eISBN: 978-1-4514-1647-3